Integration of LC/MS, NMR and Molecular Docking for Profiling of Bioactive Diterpenes from Euphorbia mauritanica L. with in Vitro Anti‐SARS‐CoV‐2 Activity. Issue 2 (23rd January 2023) - Essa, Ahmed F.; El‐Hawary, Seham S.; Kubacy, Tahia M.; El‐Din A. M. El‐Khrisy, Ezz; El‐Desoky, Ahmed H.; Elshamy, Abdelsamed I.; Younis, Inas Y.
Abstract: In spite of tremendous efforts exerted in the management of COVID‐19, the absence of specific treatments and the prevalence of delayed and long‐term complications termed post‐COVID syndrome still urged all concerned researchers to develop a potent inhibitor of SARS‐Cov‐2. The hydromethanolic extracts of different parts of E. mauritanica were in vitro screened for anti‐SARS‐Cov‐2 activity. Then, using an integrated strategy of LC/MS/MS, molecular networking and NMR, the chemical profile of the active extract was determined. To determine the optimum target for these compounds, docking experiments of the active extract's identified compounds were conducted at several viral targets. The leaves extract showed the best inhibitory effect with IC50 8.231±0.04 μg/ml. The jatrophane diterpenes were provisionally annotated as the primary metabolites of the bioactive leaves extract based on multiplex of LC/MS/MS, molecular network, and NMR. In silico studies revealed the potentiality of the compounds in the most active extract to 3CLpro, where compound 20 showed the best binding affinity. Further attention should be paid to the isolation of various jatrophane diterpenes from Euphorbia and evaluating their effects on SARS‐Cov‐2 and its molecular targets. Abstract :